2012
DOI: 10.1111/j.1939-3938.2011.01125.x
|View full text |Cite
|
Sign up to set email alerts
|

De-escalation and limit-setting in forensic mental health units

Abstract: Limit-setting and de-escalation are commonly used nursing interventions that are critical to the effective maintenance of the therapeutic milieu and the prevention and management of aggression in forensic mental health units. However, despite their purported importance, the techniques used in these interventions are rarely described. Further, these techniques are seldom based on empirical research or derived from a theory or model of aggression or interpersonal behavior. The purpose of this review is to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…Being aware of one's own tone of voice and body language are both indicated as part of verbal de‐escalation, as is remaining calm and being non‐confrontational (Price & Baker ). Similarly, good communication skills and providing a safe place for de‐escalation to take place are both regularly cited as cornerstones of de‐escalation (; Roberton et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Being aware of one's own tone of voice and body language are both indicated as part of verbal de‐escalation, as is remaining calm and being non‐confrontational (Price & Baker ). Similarly, good communication skills and providing a safe place for de‐escalation to take place are both regularly cited as cornerstones of de‐escalation (; Roberton et al ).…”
Section: Discussionmentioning
confidence: 99%
“…The management of aggression in inpatient settings is based on two core concepts, namely de-escalation and limit-setting. What was very interesting, therefore, was that a recent review of the use of de-escalation and limitsetting in inpatient psychiatric settings found that there was very little by way of an empirical evidence base to demonstrate that any techniques commonly used and/or advocated actually worked (Roberton et al 2012). However, in place of this, there are a series of clinical practice guidelines, which have been drawn from the collective clinical wisdom of experienced mental health clinicians (NICE Clinical Guideline 25 2005).…”
Section: The Management Of Aggression In Psychiatric Servicesmentioning
confidence: 96%
“…Finfgeld-Connett (2009) and other authors (Johnson and Delaney 2007) have also reported that de-escalation strategies are more successful when communicating with the person in a respectful, empathic, calm and controlled manner. By embracing reciprocity, authenticity, simple and direct instructions, and fostering patient choice through providing options, this type of therapeutic stance has contributed to better outcomes (Lancee et al 1995, Roberton et al 2012). This stance links in neatly with more recent research into the application of interpersonal theory, considered along indices of affiliation and control, to the management of aggression (Kiesler 1983).…”
Section: Communicationmentioning
confidence: 98%
See 2 more Smart Citations